Case With Transthyretin Amyloid Cardiomyopathy Complicated With Rapidly Progressive Aortic Stenosis Possibly Caused by Amyloid Deposition in the Aortic Valve. (November 2021) - Fujimoto, Tomotaka; Yamano, Tetsuhiro; Miyagawa-Hayashino, Aya; Naiki, Hironobu; Ueda, Mitsuharu; Tasaki, Masayoshi; Yamano, Michiyo; Zen, Kan; Numata, Satoshi; Matoba, Satoaki
Abstract : Supplemental Digital Content is available in the text.